Effect of berbamine on invasion and metastasis of human liver cancer SMMC-7721 cells and its possible mechanism. Issue 1 (January 2022) - Yu, Bin-bin; Liu, Li-li; Yan, Jia-dong; Cao, Jian-bo; Cao, Ying
Abstract : Berbamine is a bisbenzylisoquinoline alkaloid extracted from Berberis poiretii of Berberis of Berberidaceae. It has been reported that it can significantly inhibit the proliferation of a variety of malignant tumor cells, including liver cancer. However, the effect of berbamine on the invasion and metastasis of liver cancer has not been reported. The present study demonstrated that berbamine inhibited the migration and invasion of SMMC-7721 cells in a concentration-dependent manner and obviously increased the gap junction function and the expression of Cx32 in SMMC-7721 cells compared with control group. However, after silencing Cx32, berbamine had no significant effect on cell invasion and metastasis. Before silencing Cx32, the expression of PI3K and P-AKT were decreased after berbamine treated on SMMC-7721 cells for 24 h. After silencing Cx32, the expression of PI3K and P-AKT were increased in SMMC-7721 cells. The expression of PI3K and P-AKT had no significant effect after berbamine treated on SMMC-7721 cells for 24 h with silencing Cx32. In conclusion, the results of the present study suggest that berbamine could inhibit the SMMC-7721 cell migration and invasion, and its mechanism may be related to the regulation of PI3K/AKT signaling pathway by enhancing the expression of Cx32.